Population dynamics and structure of sperm whale (Physeter macrocephalus) in Mediterranean Sea ... - VIOLI, BIAGIO (Universit degli studi di Genova, 2020)
The sperm whale (Physeter macrocephalus) has a cosmopolitan distribution. In the Mediterranean, sperm whale sub-population is classified as ?Endangered? according to the International Union for the Conservation of Nature. Even though this population hasn?t faced the whaling age, it is currently threatened by other anthropogenic impacts, which cause direct mortality and strandings (i.e. ship strikes, debris ingestion, entanglement in driftnets), or may cause indirect mortality (e.g. noise pollution). Previous genetic, acoustic and mark-recapture studies have indicated that this population is distinct from the North Atlantic population. Within the Mediterranean Sea, the population structure is however unclear. Photo-ID data have shown three recaptures between the eastern and the western basins, but no confirmation of breeding success between those basins is available to date. Genetic differentiation within the Mediterranean Sea has already been confirmed for various dolphin and fish species. Here, we ...